Role of the polymer degradation processes in environmental pollution and waste treatment - Vasile, C. (Polimery, 2022)
The effect of various processes of environmental degradation of polymers (under atmospheric conditions, in water, soil, living organisms) on the pollution of the environment has been characterized. Activities concerning utilization of plastics wastes have been described. Some problems concerning the use of photo- and biodegradable polymers have been discussed. The results of author's research works on the course of degradation of poly-olefins (PE, i-PP) or epoxy resin (ER) with addition of various amounts of lignin modified with epoxy groups are presented as well as the effect of such blends on the plants growth. Except the positive influence on vegetative mass also significant detrimental effects occurring during blossom period have been observed.